2020
DOI: 10.2147/nds.s261229
|View full text |Cite
|
Sign up to set email alerts
|

<p>Prevalence of Vitamin D Deficiency Among Iranian Pregnant Women</p>

Abstract: Background: Vitamin D deficiency (VDD) is a common concern. A high prevalence of VDD has been reported among pregnant women in different countries. The aim of this study was to assess the prevalence of VDD in the first trimester of pregnancy. Methods: This cross-sectional study was conducted on 267 pregnant women (before 14 weeks of gestation). The level of 25-hydroxyvitamin D (25(OH)D) was measured. Demographic data (age, educational level, season of blood sampling, and vitamin D supplementation intake) were … Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

0
10
0

Year Published

2021
2021
2024
2024

Publication Types

Select...
5
1

Relationship

0
6

Authors

Journals

citations
Cited by 9 publications
(10 citation statements)
references
References 30 publications
0
10
0
Order By: Relevance
“…The correlation between vitamin D levels and season of birth was also reported by Korj-Bulos et al They showed low levels of vitamin D in neonates who were born during winter months ( 11 ). Other studies demonstrated higher prevalence of vitamin D deficiency in colder seasons ( 9 , 11 ). However, some other researchers did not find any significant differences between season of birth and the vitamin D level ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 86%
See 1 more Smart Citation
“…The correlation between vitamin D levels and season of birth was also reported by Korj-Bulos et al They showed low levels of vitamin D in neonates who were born during winter months ( 11 ). Other studies demonstrated higher prevalence of vitamin D deficiency in colder seasons ( 9 , 11 ). However, some other researchers did not find any significant differences between season of birth and the vitamin D level ( 30 , 31 ).…”
Section: Discussionmentioning
confidence: 86%
“…The prevalence of vitamin D deficiency in pregnant women in Middle Eastern countries is high and is estimated to be 60-80% ( 7 , 8 ). Among Iranian pregnant women, the prevalence rates of vitamin D deficiency have been demonstrated as 78%, 76%, 70.4% and 69.2% by several studies ( 9 ). Deficiency of vitamin D in pregnant women decreases the transfer of this vitamin through the placenta and at birth ( 10 - 12 ).…”
Section: Introductionmentioning
confidence: 99%
“…Vitamin D and Ca play vital roles in women’s overall health due to the effect of Ca on bone health and the role of vitamin D in the hemostasis of Ca as well as in women’s reproductive health ( 23 , 24 ). The prevalence of vitamin D deficiency has been reported to be around 75.1% among Iranian women ( 25 ). According to the study findings, 48.8% of participants had vitamin D deficiency.…”
Section: Discussionmentioning
confidence: 99%
“…In Middle Eastern countries, VDD among pregnant women is an estimated 60–80% [ 9 , 10 ]. Among Iranian pregnant women, studies have reported prevalence rates of 78%, 76%, 70.4%, and 69.2% [ 11 ]. The estimated prevalence in pregnant women in the USA and Canada was reported to be 42–72% [ 12 ].…”
Section: Introductionmentioning
confidence: 99%